PENGARUH INVESTASI, UPAH MINIMUM DAN IPM TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI KALIMANTAN BARAT - Reni Helvira; Endah Putri Rizki (Fakultas Ekonomi dan Bisnis Islam, 2020)
Introduction: This study ains to determine : 1) the effect of Investment on Unemployment Rate in West Kalimantan, 2) the effect of the Minimum Wages on the Unemployment Rate in West Kalimantan and 3) the effect of the Human Development Index (HDI) Rate in West Kalimantan. Background Problems: Unemployment is a problem faced by all countries in the word, especially in developing countries, one of which is Indonesia. Unemployment is a complex problem that is influeneed by various interrelated factors, including the lack of available jobs, education and ability ini their expertise. The unemployment rate in West Kalimantan is still quite high, which is ranked nineteen out of thirty-four Provinces. Research Methods: Descriptive and associative methods with a quantitative approach by using the econometrics model are used in this study to find out the effect of independent variables on the dependent variable. The analytical method in this study uses panel data regression analysis that uses eross section data, that is representing fourteen districts/cities in West Kalimantan and time series data from 2008 to 2017. Results: this study indicate that the variables of economic growth, minimum wages and the index of human development index simultaneously (together) significantly influence the level of open unemployment in West Kalimantan. Then, partially (individually) the investments variable has a positive and not significant effect on the level of open unemployment in West Kalimantan, the minimum wage has a positive and significant effect on the level of open unemployment in West Kalimantan and the human development index has a negative and not significant effect on the level of open unemployment in West Kaliamnatan. Conclusion:. The minimum wage is a factor affecting unemployment in West Kalimantan compared to other variables such as investment and HDI.